BUDI PEKERTI SEBAGAI PRIORITAS LIFELONG LEARNING DALAM GEGURITAN SALAMPAH LAKU - Sugiharta, I Putu Suweka Oka (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
In general, there are two main mistakes in the world of education today: apathy towards character development or, conversely, a rush towards the divine dimension. In the first error, education, whether overtly or covertly, is separated from the attainment of good character. Education is only aimed at producing superior people who will bring technological progress to society. Even though students do not have adequate manners, if they are smart, they are considered tolerable. On the other hand, even though you have good manners but do not have sufficient intelligence, you are considered unable to contribute to society. Meanwhile, in the second mistake, education is based on rigid dogmas related to divinity. Students are not given the freedom to interpret these dogmas and are only required to follow them. Often, this method only focuses on the abstract world and forgets about real life, including cultivating morals. Moral teachings can actually balance both worldly intelligence and belief in divinity. Through moral teachings, intelligent people with character and religious figures who are far from blind fanaticism can be formed. In Geguritan Salampah Laku, it is stated that complete learning must be pursued throughout life. The priority for successful learning at each stage is an increasingly established character. This type of research is qualitative with a textual approach